Reasonable design of ZnO decorated hollow porous carbon nanofibers for stable lithium metal anode. (1st March 2023) - Song, Xinrui; Wen, Jiaming; Li, Xiaohua; Zou, Jizhao; Yan, Chaobo; Zeng, Xierong
Abstract: The commercial applications of lithium metal anodes are still hindered by safety concerns resulting from uncontrollable lithium dendrite growth and serious volume changes during the discharge and charge processes. In this study, N-rich hollow porous carbon nanofibers decorated with various zinc oxide morphologies as the lithiophilic phase are fabricated through simple coaxial-electrospinning. The ZnO nanostructure gradually changes from small nanoparticles to needle-like structures with increasing Zn(Ac)2 fraction, resulting in lithiophilic to lithiophobic scaffold transfer, owing to current density concentration, long Li ion diffusion distances, and inhomogeneous Li deposition behavior with ZnO needle-like shapes. The small ZnO nanoparticles on the NHCNF as the Li metal deposition scaffold also efficiently reduce the local current density and guide the Li ions to homogenously nucleate and deposit. The hollow porous structure provides ultra-high Li metal space accommodation, which can prevent uncontrollable Li dendrite growth. These excellent scaffold characteristics display a high Columbic efficiency of 97% after 150 cycles at 1 mA cm −2 and a stable cyclic lifespan of 1000 cycles in the symmetrical cells, even at a super high current density of 5 mA cm −2 on the 5-ZnO@NHCNF/Li composite anode, full cells coupled with an LiFePO4 commercialized cathode deliver excellent cyclic and rate performance.